تحسين كفاءة اللغة العربية لدى الطلاب الإندونيسيين عبر المسرحية - Attaqi, Khonsa Fillah; Ala’ Ulloh, Faidhul Mahdhi; Mufidah, Nuril (Proceeding of International Conference on Islamic Education (ICIED); Vol 8 No 1 (2023): Proceeding of International Conference on Islamic Education (ICIED), 2023)
Arabic has long existed in Indonesia from the spread of Islam brought by the Walisongo to this day. Increasingly, Arab existence has become more optimized with several Arabic learning innovations, one of which is Mashrohiyah. Mashrohiyah or role-playing is widely applied to colleges in Indonesia as an compulsory course to develop potential students from the development of creativity to the benefit of kalam as a optimizing form of Arabic in Indonesia. This article aim to describes the optimalization of student Arabic competence in Indonesia through Mashrohiyah. One approach used in mashrohiyah is a Theory of sociodramatic, an innovative and creative learning method of role-playing to break the social phenomena that surround the environment. For the implementation of teaching, masrohiyah has a long stage which must be prepared months before it is performed, this stage includes making and translating the script, making a theme songs, and then the rehearsal stage (script analysis and deepening the role). After a whole preparation, the mashrohiyah is ready to be held and watched by the audiences. Mashrohiyah was able to develop maharah kalam students because they were required to exchange Arabic so that they could speak Arabic spontaneously if something went off the chart. In addition, the mashrohiyah arrangement was able to introduce Arabic to the public so that many people had more interest in learning Arabic.